Effects of Electric Field During Incubation of Eggs on the Hatchability and Post-Hatch Performance of Meat Chickens - Shafey, T.M.; Shalaby, M.I.; Bayoumi, M.S. (International Journal of Poultry Science, 2007)
The effects of electric field (EF) during incubation of eggs on hatchability traits, and post-hatch performance, nutrient utilization and carcass characteristics of meat chickens were investigated in 2 trials. Eggs from a meat-type breeder flock were incubated under EF of 30kV/m, 60Hz during the first 18 d of incubation as compared with the control incubation treatment (C). Chicks hatched from the two incubation treatments (EF and C) were fed ad libitum and their performance was monitored. Measurements were made of hatchability, hatchability failures, chick hatching weight (CHWT), length of incubation, post-hatch performance [weight gain (WTG), feed consumption, and feed conversion ratio (FCR)], and nutrient utilization (apparent nitrogen retention and nitrogen corrected metabolizable energy of birds at 30 d of age), and carcass characteristics of sexed birds at 40 d of age. EF incubation of eggs significantly (P < 0.05) increased per cent of hatchability, per cent of hatching chicks by 468 hour of incubation, CHWT and reduced embryo deaths, pips with life embryos, length of incubation and percentage of hatched chicks at 492 plus 504 of incubation by approximately 11.0, 428, 2.4, 56, 86, 5.1 and 98%, respectively. EF birds had a higher (P < 0.05) WTG than the C birds, when they were placed with feed and water after hatching, but not when birds were held without feed and water to the end of incubation period. EF incubation of eggs did not significantly influenced feed intake, FCR, and nutrient utilization of birds. Carcass of the EF birds had higher (P < 0.01) proportion of drumstick [g/kg eviscerated carcass (EC)], and lower proportions of edible offal (liver plus heart plus gizzard, g/kg live weight (LWT) and thigh (g/kg EC) when compared with those of the C birds. Carcass of male birds had significantly (P < 0.01) higher proportion of drumstick (g/kg EC), and lower proportion of edible offal (g/kg LWT) than female birds. In the EF group, female birds had significantly (P < 0.01) higher LWT and carcass neck plus back (g/kg EC), and lower EC (g/kg LWT) and carcass breast (g/kg EC) than males birds. However in the C group, male birds had a higher LWT than female birds. Whilst, sex of birds of the C group did not significantly influence EC (g/kg LWT), and carcass breast and back plus neck (g/kg EC). It is concluded that the incubation of eggs under EF of 30kV/m, 60Hz increased hatchability of eggs, and chick hatching weight, reduced incubation time of eggs and altered carcass characteristics of birds. EF incubation of eggs increased weight gain of birds when hatched chicks were placed with feed and water after hatching. EF incubation of eggs did not altered feed efficiency, and nutrient utilization of meat chickens.